IMPROVING STUDENTS’ VOCABULARY BY MAKING CLIPPING AS NEWS READER OF FIRST SCIENCE CLASS - Fitrah Yuliawati; Ika Nuriyanti (IKIP Siliwangi, 2021)
Several problems of Vocabulary are found in the first science class in SMAN 2 Pamekasan. The students` felt bored to study and difficult to memorize vocabulary are general problem. To solve the problems an action research was conducted by the researcher and the teacher by using clipping as news reader to develop students` vocabulary. Therefore, the problem of this research is about how the clipping implementation as news reader can develop students’ vocabulary. And the aim was to develop students’ vocabulary in English. Based on the result of test in In the preliminary study there was 21% only who passed, in cycle 1 students get achievement 42% (10 students) who passed the minimum score (KKM, 75), it was increased to the second cycle 92 % (22 Students) who passed the target score (KKM, 75) and there 2 students only who were still failed. So the researcher and teacher decided that the implementation of making clipping as news reader technique can develop students’ vocabulary of first science class in SMAN 2 Pamekasan. Keywords: Making Clipping, News Reader, Vocabulary, Science Class